2007
DOI: 10.1177/1933719106298687
|View full text |Cite
|
Sign up to set email alerts
|

Val153Met Polymorphism of Catechol-O-Methyltransferase and Prevalence of Uterine Leiomyomata

Abstract: The catechol-O-methyltransferase (COMT) gene encodes enzymes that inactivate catechol estrogens and may have a protective role in estrogen-induced tumorigenesis, such as uterine leiomyoma (fibroids). Val158Met is a common single-nucleotide polymorphism of the COMT gene (Ex4-12 G>A; rs4680) that results in a lower activity enzyme, increasing susceptibility to tumorigenesis. The purpose of this study was to evaluate the relation between the COMTVal158Met polymorphism and uterine fibroids. Participants were 972 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Semiquinones, quinones, and radicals cause genomic mutations and cell damage. The mechanisms of COMT in hormone-dependent UL reported in previous studies are generally accepted [15,16]. At least 8 SNP loci can be found in the coding region of COMT gene.…”
Section: Discussionmentioning
confidence: 89%
“…Semiquinones, quinones, and radicals cause genomic mutations and cell damage. The mechanisms of COMT in hormone-dependent UL reported in previous studies are generally accepted [15,16]. At least 8 SNP loci can be found in the coding region of COMT gene.…”
Section: Discussionmentioning
confidence: 89%
“…A large number of genes have been suggested to be associated with risk of ULM, and the COMT gene is one of them (Cong et al, 2012;Huang et al, 2010;Je et al, 2012). The Val158Met polymorphism in the COMT gene has been identified to be associated with risk of ULM, but the results were inconclusive (Al-Hendy and Salama, 2006b; Denschlag et al, 2006;Gooden et al, 2007). In addition, there is still no meta-analysis to investigate these associations.…”
Section: Discussionmentioning
confidence: 94%
“…Carriage of the mutant COMT G1947A allele results in a 3-4 fold lower enzyme activity of COMT (Lachman et al, 1996). Many studies have suggested that the Val158Met polymorphism was associated with susceptibility to ULM (Al-Hendy and Salama, 2006b;Denschlag et al, 2006;Gooden et al, 2007); however, the results were inconclusive, especially in populations from different ethnical backgrounds. Meta-analysis is a useful method for investigating associations between genetic factors and diseases (Cao et al, 2013;Chen et al, 2013;Nie et al, 2013), because it uses a quantitative approach to combine the results of different studies on the same topic, and potentially provide more reliable conclusions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Tumoral molecular biology studies suggest that E 2 metabolism may be altered in women of African origin, because polymorphism in the catecholamine-O-methyl transferase (COMT) gene leading to reduced enzyme activity has been correlated with increased tumor size (53). However, this polymorphism does not appear to alter fibroid prevalence (54). The product of E 2 transformation by COMT, 2-methoxy-E 2 , has been shown to be involved in the regulation of aromatase activity and estrogen signaling in fibroids.…”
Section: Risk Factors For Fibroidsmentioning
confidence: 98%